Method for preparing flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots and applications thereof

By preparing hyperbranched polymer-based carbonized polymer dots modified with flexible disulfide bonds, the problems of low fluorescence quantum yield and insufficient sensitivity were solved, realizing efficient quantitative detection and antibacterial function of ferric ions. This method is suitable for rapid and low-cost detection of meat by-products and food preservation.

CN121022398BActive Publication Date: 2026-01-27INST OF AGRO FOOD SCI & TECH CHINESE ACADEMY OF AGRI SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511546819.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-28
Publication Date
2026-01-27
Estimated Expiration
2045-10-28

AI Technical Summary

Technical Problem

Existing fluorescent carbonized polymer dots (CPDs) materials have low fluorescence quantum yield and insufficient sensitivity, making it difficult to meet the demand for efficient, convenient, and low-cost quantitative detection of iron ions in meat by-products. Furthermore, traditional methods are cumbersome to operate, expensive to use, and have low detection efficiency.

Method used

By preparing flexible disulfide bond-modified hyperbranched polymer-based carbonized polymer dots, utilizing disulfide bonds to regulate the flexibility of the main chain, and combining hydrothermal solvent method and surface modification technology, carbonized polymer dots with high fluorescence quantum yield and antibacterial properties were prepared, realizing quantitative detection of ferric ions and antibacterial function.

Benefits of technology

This invention enables simple and rapid quantitative detection of ferric ions, improves fluorescence quantum yield and detection sensitivity, exhibits good antibacterial effects, and expands the application prospects of the material in food preservation and safety monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121022398B_ABST
    Figure CN121022398B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dot, and belongs to the technical field of nano fluorescent materials, and aims to solve the problems of complicated operation, expensive equipment and low fluorescent quantum yield and insufficient sensitivity of existing carbonized polymer dots caused by difficulty in main chain flexibility regulation in traditional iron ion detection methods. The method controls the molar ratio of 1,6-hexanediamine and bisacryloyl cystamine to regulate the number of disulfide bonds of the hyperbranched polyamide-amine precursor, and then performs nitrogen hetero-Michael addition reaction with tris(2-aminoethyl)amine to form a flexible main chain structure, and then performs acid treatment, citric acid hydrothermal carbonization and ion exchange purification steps to obtain the carbonized polymer dot with high fluorescent quantum yield and main chain flexibility. The obtained material can be used for high-sensitivity quantitative detection of ferric ions in meat by-products (liver, blood and the like) and the field of microbial antibacterial.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new materials technology, specifically to a method for preparing and applying flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots. Background Technology

[0002] Meat by-products (such as liver, kidney, and blood) are rich in iron, an essential element for the human body. Accurate detection of iron content is crucial for assessing nutritional value and safety. Current mainstream methods for quantitative iron ion detection (such as atomic absorption spectrometry and inductively coupled plasma mass spectrometry) suffer from cumbersome and time-consuming operations, reliance on expensive large-scale instruments, and low detection efficiency, failing to meet the demand for rapid and low-cost detection. In recent years, detection methods based on fluorescent carbonized polymer dots (CPDs) have attracted attention due to their simplicity and potential cost advantages. However, existing CPD materials generally face the bottleneck of low fluorescence quantum yield, which limits detection sensitivity. The core challenge lies in the lack of effective means to precisely control the flexibility of the precursor polymer backbone, a property that directly affects the intramolecular motion and final optical properties of the material. Therefore, developing a novel fluorescent probe material and its preparation method that can simultaneously overcome the shortcomings of traditional methods and solve the problems of low quantum yield and difficult performance control of CPDs is a key challenge for achieving efficient, convenient, and low-cost quantitative detection of iron ions in meat by-products. Summary of the Invention

[0003] This invention provides a method for preparing flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots, aiming to solve the problems of cumbersome operation, expensive equipment, and low detection efficiency of traditional methods (such as atomic absorption spectrometry) in the detection of iron ions in meat by-products. At the same time, it overcomes the defects of existing carbonized polymer dots (CPDs) in low fluorescence quantum yield and insufficient sensitivity due to the difficulty in controlling the flexibility of the main chain.

[0004] The existing fluorescent probes for detecting ferric ions suffer from narrow linear response range and limited sensitivity due to insufficient backbone flexibility and coordination site density, making it difficult to meet the quantitative requirements for trace iron ions in complex food matrices.

[0005] The problem is that conventional antibacterial agents require high concentrations to be effective and are difficult to integrate with fluorescence detection functions, resulting in limited application scenarios for materials and the inability to achieve a synergistic effect of "detection-antibacterial".

[0006] The problem is that silane coupling agents are prone to self-aggregation or physical adsorption when directly added to hydrothermal systems, which leads to uneven surface modification and reduces the stability and functional consistency of the coating layer.

[0007] The problem is that residual solvents and uncondensed silanols in the pre-hydrolyzed solution can interfere with the crosslinking reaction, causing pore defects or insufficient mechanical strength in the coating layer, and accelerating material aging.

[0008] The problem is that the concentration of the pre-hydrolyzed solution lacks quantitative indicators, excessive condensation leads to a sharp increase in viscosity and uneven dispersion during dropwise addition, while insufficient condensation reduces the crosslinking density and weakens the protective effect of the coating layer.

[0009] The problem is that the endpoint of the silane crosslinking reaction is unclear, and residual active groups may cause side reactions or quench fluorescence, while also affecting the surface exposure efficiency of the antibacterial groups.

[0010] To achieve these and other advantages according to the present invention, a method for preparing flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots is provided, comprising the following steps:

[0011] Step 1: Dissolve a mixture of 1,6-hexanediamine and bisacryloylcysteine ​​in methanol and mix thoroughly. Then carry out a nitrogen-Michael addition reaction at 25°C to 35°C for 48 to 96 hours under nitrogen atmosphere to prepare hyperbranched polyamide-amine with disulfide bonds.

[0012] The molar ratio of the mixture of 1,6-hexanediamine and bisacryloylcysteine ​​to tris(2-aminoethyl)amine is 1:1.1 to 1:1.2; the molar ratio of 1,6-hexanediamine to bisacryloylcysteine ​​in the mixture is 0.1:4 to 4:0.1.

[0013] Step 2: Add 0.05-0.2 mol / L L-cysteine ​​hydrochloride-sodium citrate buffer dropwise to the product obtained in Step 1 until pH=2. After vacuum filtration, dry the product under vacuum at 40°C for 24 to 48 hours to obtain white or light yellow hyperbranched polyamide-amine hydrochloride powder.

[0014] Step 3: Mix citric acid with the branched polyamide-amine hydrochloride powder at a mass ratio of 2:5 to 10:3, using pure water as a solvent, and carry out a hydrothermal reaction at 80°C to 150°C for 1 to 8 hours; simultaneously add N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, wherein the mass of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 5% to 15% of the citric acid.

[0015] Step 4: After cooling the reaction product to room temperature, filter it. First, pre-filter it through a cellulose ester membrane with a molecular weight cutoff of 1 kDa, and then dialyze it for 24 to 48 hours in a circulating pure water system containing a strong acid cation exchange resin using a dialysis bag with a molecular weight cutoff of 800 to 1000 Da. After freeze-drying the dialysate, flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots are obtained.

[0016] The number of disulfide bonds in the carbonized polymer sites of the flexible disulfide bond-modified hyperbranched polymer was controlled by adjusting the molar ratio of 1,6-hexanediamine to bisacryloylcysteine.

[0017] Flexible disulfide bonds refer to flexible chain segments containing dynamic disulfide bonds.

[0018] Preferably, in the preparation method of flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots of the present invention, the molar ratio of the mixture of 1,6-hexanediamine and bisacryloylcysteine ​​to tris(2-aminoethyl)amine in step one is 1:1.1, the reaction conditions are 25°C, and the reaction time is 50 h under nitrogen protection.

[0019] Preferably, in the preparation method of flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots of the present invention, the mass ratio of citric acid to hydrochloride powder in step three is 2:1, the reaction temperature is 130°C, and the reaction time is 6 hours.

[0020] This invention also provides an application of flexible disulfide bond-modified hyperbranched polymer-based carbonized polymer dots in the quantitative detection of ferric ions in meat by-products (liver, blood, etc.), comprising the following steps: adding a ferric ion standard solution with a concentration of 0-300 μmol / L to an aqueous solution of flexible disulfide bond-modified hyperbranched polymer-based carbonized polymer dots and mixing, incubating at 25°C for 30 min, detecting the change in fluorescence intensity using a fluorescence spectrophotometer, and establishing a linear relationship model between ferric ion concentration and fluorescence intensity; the disulfide bond content in the flexible disulfide bond-modified hyperbranched polymer-based carbonized polymer dots is positively correlated with the detection sensitivity of ferric ions.

[0021] The present invention also provides an application of flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots in antibacterial activity, wherein the concentration of the flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots is ≥0.05 mg / mL.

[0022] Preferably, in the preparation method of the flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots of the present invention, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane needs to be pre-hydrolyzed before addition: N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and anhydrous ethanol are mixed at a volume ratio of 1:5, and L-cysteine ​​hydrochloride-sodium citrate buffer solution with pH=2.0 is added until the final concentration of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 0.1 mol / L. The mixture is then magnetically stirred in an ice-water bath at 0~5℃ for 5~10 minutes to obtain a pre-hydrolyzed solution.

[0023] The pre-hydrolyzed solution is added dropwise to the hydrothermal reaction system in step three within 30 minutes, with the dropping rate controlled at 0.5 mL / min to 2 mL / min. After the addition is complete, the reaction system is heated to 80 to 150 °C and the reaction continues for 1 to 8 hours to complete the surface directional modification.

[0024] Preferably, in the preparation method of the flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots of the present invention, the pre-hydrolyzed solution needs to undergo the following treatment before being added dropwise to the reaction system in step three:

[0025] The pre-hydrolyzed solution was placed in a rotary evaporator at 30-35℃ with a vacuum of -0.09-0.1 MPa. Ethanol was removed by distillation until the volume of the distillate reached 45%-50% of the initial volume of the pre-hydrolyzed solution. Hexamethyldisilazane and 0.1 wt% polyethylene glycol-2000 were added to the concentrate. The amount of hexamethyldisilazane added was 0.1-0.3 times the volume of the concentrate. The mixture was stirred at 0-5℃ for 20-30 minutes. The pre-hydrolyzed solution was then added dropwise to the reaction system under nitrogen protection within 30 minutes.

[0026] Preferably, in the preparation method of flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots of the present invention, the vacuum degree is controlled at -0.095±0.002MPa during the rotary evaporation to remove ethanol; the distillation endpoint is determined by the viscosity of the concentrate reaching 50±2cP, and the viscosity is measured at 25°C using a Brookfield viscometer (rotor LV3, rotation speed 60rpm).

[0027] Preferably, in the preparation method of the flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots of the present invention, the mass ratio of hexamethyldisilazane to polyethylene glycol-2000 is 1:0.8 to 1:1; the stirring reaction is carried out at 0-5°C, and the reaction endpoint is determined by the pH value of the reaction solution rising to 6.5±0.2, and a covalent cross-linked network coating structure of siloxane and polyethylene glycol is generated.

[0028] The present invention has at least the following beneficial effects:

[0029] 1. This invention uses disulfide-bond functionalized hyperbranched polyamide-amine as the precursor material for carbonized polymer dots. By precisely adjusting the disulfide bond content in the main chain structure of the hyperbranched polymer, a model of ssHPA-CPDs with differences in main chain flexibility was successfully established. Using hyperbranched polyamide-amine as the same source of nitrogen and sulfur diatoms, and citric acid as the carbon source, flexible disulfide-bond modified hyperbranched polymer-based carbonized polymer dots (ssHPA-CPDs) emitting blue light were successfully prepared by adjusting different reaction times, reaction temperatures, and concentrations of hyperbranched polyamide-amine. Finally, utilizing its simple and rapid fluorescence signal response, trivalent iron ions (Fe3+) were detected. 3+ This method enables quantitative detection of [unspecified substance], thus avoiding complex and cumbersome operating procedures, long detection times, and the consumption of expensive equipment and experimental consumables. Simultaneously, using hyperbranched polyamide-amines rich in terminal amine groups as a synthetic precursor, nitrogen-sulfur dual heteroatom-doped carbonized polymer dots exhibit excellent antibacterial properties.

[0030] 2. This invention successfully prepared flexible disulfide-modified hyperbranched polymer-based carbonized polymer dots (ssHPA-CPDs) using a hydrothermal solvent method. The disulfide bond (S–S bond) has a longer bond length (~2.05 Å) than the C–C bond (~1.54 Å), a lower bond energy (~268 kJ / mol), and more flexible bond angles, resulting in improved molecular chain mobility and enhanced flexibility. By altering the disulfide bond content in the hyperbranched polyamide-amine, the main chain flexibility of the hyperbranched polyamide-amine can be controlled, thereby regulating the fluorescence performance and increasing the quantum yield of ssHPA-CPDs. The fluorescence signal is altered by utilizing the coordination interaction between ferric ions and ssHPA-CPDs, achieving quantitative detection of ferric ions with good results. This method is simple, rapid, and reproducible, avoiding the drawbacks of complex preparation processes, expensive equipment, and low efficiency. Furthermore, the numerous terminal amine groups of hyperbranched polyamide-amine carry a positive charge under physiological conditions, which can bind to the negatively charged bacterial cell membrane, disrupt the membrane structure, cause leakage of contents, and ultimately kill the bacteria, thus simultaneously achieving antibacterial function and exhibiting good antibacterial effect. It has potential application prospects in fields such as analytical detection and antibacterial properties.

[0031] 3. This invention precisely optimizes the main chain flexibility by controlling the number of disulfide bonds, thereby enhancing molecular chain mobility and electronic transition efficiency, achieving high fluorescence quantum yield (e.g., 29.08%) and detection sensitivity (detection limit < 0.1 μM). Using hyperbranched polyamide-amine as a unified nitrogen and sulfur source, and synergistically carbonizing with citric acid, the material is endowed with specific ferric ion response capabilities and antibacterial activity.

[0032] 4. This invention specifies a molar ratio of 1,6-hexanediamine and bisacryloylcysteine ​​to tris(2-aminoethyl)amine of 1:1.1 and a reaction condition of 25℃ / 50h to ensure efficient and directional formation of disulfide bonds and improve the uniformity of the product structure. The amine matrix protonation degree of the hyperbranched polyamide-amine hydrochloride powder is stable, providing a reliable precursor for subsequent carbonization, and the batch fluorescence intensity fluctuation (RSD) is significantly reduced.

[0033] 5. In this invention, the mass ratio of citric acid to branched polyamide-amine hydrochloride powder is 2:1, and the hydrothermal parameters of 130℃ / 6h are optimized to achieve the carbon core size and surface functional group density, resulting in peak fluorescence intensity. The citric acid is fully carbonized to form a rigid luminescent core while retaining the flexible amine shell, thus balancing optical performance and antibacterial function.

[0034] 6. In this invention, the disulfide bond content is positively correlated with the detection sensitivity of ferric ions, and the flexible backbone enhances the accessibility of coordination sites. A stable linear response is established over a wide concentration range of 0-300 μM, exhibiting strong resistance to food matrix interference and a recovery rate >95%.

[0035] 7. In this invention, the densely packed amine groups at the ends of the hyperbranched structure carry a positive charge under physiological conditions, disrupting the bacterial membrane structure. A concentration of 0.05 mg / mL can achieve an inhibition rate of >90%. The material simultaneously maintains fluorescence detection functionality, expanding its application to integrated food preservation and safety monitoring.

[0036] 8. In this invention, the pre-hydrolysis treatment promotes the conversion of silane into active silanol, achieving directional covalent bonding with amine groups. The coating layer has a uniform thickness, reducing fluorescence quenching caused by surface defects, and improving photostability to 95% after 24 hours.

[0037] 9. In this invention, rotary evaporation removes ethanol to avoid bubble defects, and hexamethyldisilazane is cross-linked with polyethylene glycol-2000 (HMDS / PEG-2000) to construct a three-dimensional network. The mechanical strength of the coating layer is improved, the particle size increase is <10nm after 30 days of storage, and the precipitation rate is reduced to 7%, significantly improving the bottleneck of long-term dispersion stability of carbon dots.

[0038] 10. In this invention, the viscosity threshold (50±2 cP) precisely controls the degree of silane polymerization, ensuring the fluidity of the pre-hydrolyzed solution. During dropwise addition, a continuous coating film is formed, avoiding excessively thick or exposed areas in certain regions, thus improving batch-to-batch consistency (silane modification).

[0039] 11. In this invention, pH=6.5±0.2 indicates complete hydrolysis and cross-linking of HMDS, eliminating the quenching of fluorescence by residual silanes. The covalent cross-linking network of siloxane and polyethylene glycol improves the density of the coating layer, increases the effective exposure rate of antibacterial groups, and enhances fluorescence stability.

[0040] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description

[0041] Figure 1 The structure of the ssHPA-CPDs prepared in this invention and its response to ferric ions are shown in the schematic diagram.

[0042] Figures 2(A), 2(B), and 2(C) show the fluorescence intensity of ssHPA-CPDs prepared under different reaction conditions according to the present invention; wherein, Figure 2(A) shows the fluorescence intensity of ssHPA-CPDs prepared under different mass ratios of citric acid and hydrochloric acid powder, Figure 2(B) shows the fluorescence intensity of ssHPA-CPDs prepared under different heating times in the hydrothermal reaction, and Figure 2(C) shows the fluorescence intensity of ssHPA-CPDs prepared under different heating temperatures in the hydrothermal reaction.

[0043] Figure 3 The fluorescence quantum yield of ssHPA-CPDs prepared in this invention varies with the disulfide bond content.

[0044] Figure 4 The linear relationship of the ssHPA-CPDs prepared in this invention for detecting ferric ions is shown in the graph.

[0045] Figure 5 The image shows the antibacterial effect of ssHPA-CPDs prepared according to this invention. Detailed Implementation

[0046] The present invention will now be described in further detail with reference to the accompanying drawings, so that those skilled in the art can implement it based on the description.

[0047] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.

[0048] Example 1

[0049] A method for preparing flexible disulfide bond-modified hyperbranched polymer-based carbonized polymer dots includes the following steps:

[0050] Step 1: A mixture of 1,6-hexanediamine (HMBA) and bisacryloylcysteine ​​(CBA) is dissolved in methanol and mixed evenly. The mixture is then subjected to a nitrogen-Michael addition reaction at 30°C for 72 hours to prepare hyperbranched polyamide-amines (ssHPAs) with disulfide bonds.

[0051] The molar ratio of 1,6-hexanediamine to bisacryloylcysteine ​​in the mixture is 4:0.1.

[0052] The molar ratio of the mixture of 1,6-hexanediamine and bisacryloylcysteine ​​to tris(2-aminoethyl)amine is 1:1.15;

[0053] Step 2: Add 0.05 mol / L L-cysteine ​​hydrochloride-sodium citrate buffer dropwise to the product obtained in Step 1 until pH=2. After vacuum filtration, dry under vacuum at 40°C for 36 hours to obtain white or light yellow hyperbranched polyamide-amine (ssHPA) hydrochloride powder.

[0054] Step 3: Citric acid (CA) and the branched polyamide-amine hydrochloride powder are mixed at a mass ratio of 10:3. Using pure water as a solvent, the mixture is heated to 150°C, and an ethanol solution of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is added dropwise at a rate of 0.5 mL / min. The mixture is then subjected to a hydrothermal reaction for 1 hour. The mass of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 5% of the mass of citric acid.

[0055] Step 4: After cooling the reaction product to room temperature, filter it. First, pre-filter it through a cellulose ester membrane with a molecular weight cutoff of 1 kDa, then dialyze it for 36 hours in a circulating pure water system containing a strongly acidic cation exchange resin using a dialysis bag with a molecular weight cutoff of 900 Da. After freeze-drying the dialysate, flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots (ssHPA-CPDs) are obtained. Figure 1 As shown.

[0056] Example 2

[0057] A method for preparing flexible disulfide bond-modified hyperbranched polymer-based carbonized polymer dots includes the following steps:

[0058] Step 1: A mixture of 1,6-hexanediamine (HMBA) and bisacryloylcysteine ​​(CBA) is dissolved in methanol and mixed evenly. The mixture is then subjected to an aza-Michael addition reaction at 25°C for 50 hours under a nitrogen atmosphere to prepare hyperbranched polyamide-amines (ssHPAs) with disulfide bonds.

[0059] The molar ratio of 1,6-hexanediamine to bisacryloylcysteine ​​is 0.1:4.

[0060] The molar ratio of the mixture of 1,6-hexanediamine and bisacryloylcysteine ​​to tris(2-aminoethyl)amine is 1:1.1;

[0061] Step 2: Add 0.1 mol / L L-cysteine ​​hydrochloride-sodium citrate buffer dropwise to the product obtained in Step 1 until pH=2. After vacuum filtration, dry under vacuum at 40°C for 48 hours to obtain white or light yellow hyperbranched polyamide-amine (ssHPA) hydrochloride powder.

[0062] Step 3: Citric acid (CA) and the branched polyamide-amine hydrochloride powder are mixed at a mass ratio of 2:1. Using pure water as a solvent, the mixture is heated to 130°C, and an ethanol solution of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is added dropwise at a rate of 1 mL / min. The reaction is then carried out hydrothermally for 6 hours. The mass of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 10% of the mass of citric acid.

[0063] Step 4: After cooling the reaction product to room temperature, filter it. First, pre-filter it through a cellulose ester membrane with a molecular weight cutoff of 1 kDa, and then dialyze it for 48 hours in a circulating pure water system containing a strong acid cation exchange resin using a dialysis bag with a molecular weight cutoff of 1000 Da. After freeze-drying the dialysate, flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots (ssHPA-CPDs) are obtained.

[0064] Example 3

[0065] Step 1: A mixture of 1,6-hexanediamine (HMBA) and bisacryloylcysteine ​​(CBA) is dissolved in methanol and mixed evenly. The mixture is then subjected to a nitrogen-Michael addition reaction at 35°C for 96 hours to prepare hyperbranched polyamide-amines (ssHPAs) with disulfide bonds.

[0066] The molar ratio of 1,6-hexanediamine to bisacryloylcysteine ​​is 1:1.

[0067] The molar ratio of the mixture of 1,6-hexanediamine and bisacryloylcysteine ​​to tris(2-aminoethyl)amine is 1:1.2;

[0068] Step 2: Add 0.2 mol / L L-cysteine ​​hydrochloride-sodium citrate buffer dropwise to the product obtained in Step 1 until pH=2. After vacuum filtration, dry under vacuum at 40°C for 24 hours to obtain white or light yellow hyperbranched polyamide-amine (ssHPA) hydrochloride powder.

[0069] Step 3: Citric acid (CA) and the branched polyamide-amine hydrochloride powder are mixed at a mass ratio of 2:5. Using pure water as a solvent, the mixture is heated to 80°C, and an ethanol solution of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is added dropwise at a rate of 2 mL / min. The reaction is then carried out hydrothermally for 8 hours. The mass of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 15% of the mass of citric acid.

[0070] Step 4: After cooling the reaction product to room temperature, filter it. First, pre-filter it through a cellulose ester membrane with a molecular weight cutoff of 1 kDa, and then dialyze it for 24 hours in a circulating pure water system containing a strong acid cation exchange resin using a dialysis bag with a molecular weight cutoff of 800 Da. After freeze-drying the dialysate, flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots (ssHPA-CPDs) are obtained.

[0071] Experimental Example 1

[0072] The fluorescence intensity of ssHPA-CPDs prepared under different hydrothermal reaction conditions was measured and analyzed using a fluorescence spectrophotometer. The results are shown in Figure 2(A), Figure 2(B), and Figure 2(C). Except for the reaction conditions indicated in the figures, the other conditions are the same as in Example 2.

[0073] As can be seen from Figures 2(A), 2(B), and 2(C), the overall hydrothermal reaction conditions for the synthesis of ssHPA-CPDs show that the fluorescence intensity of ssHPA-CPDs is strongest when the mass ratio of citric acid to ssHPA hydrochloride powder is 2:1, the reaction heating time is 6 hours, and the reaction temperature is 130℃.

[0074] Experiment Example 2

[0075] The fluorescence quantum yield of ssHPA-CPDs prepared by the method of this invention was measured and analyzed using a fluorescence spectrophotometer, and the results were recorded as follows: Figure 3 As shown, different curves represent different amounts of disulfide bonds, ssHPA-CPD 0% ssHPA-CPD 25% ssHPA-CPD 50% ssHPA-CPD 75% ssHPA-CPD 100% This indicates that the number of flexible disulfide bonds in ssHPA-CPDs gradually increases, and the percentage represents the molar percentage of disulfide bonds, thereby determining the fluorescence properties of sHPA-CPDs.

[0076] based on Figure 3 It can be seen that as the disulfide bond content increases, the main chain flexibility of sHPA-CPDs is enhanced, and the fluorescence quantum yield gradually increases. Therefore, it can be deduced that the enhanced main chain flexibility and the introduction of sulfur atoms significantly enhance the fluorescence performance of sHPA-CPDs materials.

[0077] Experimental Example 3

[0078] The quantitative detection of ferric ions in meat by-products using flexible disulfide bond-modified hyperbranched polymer-based carbonized polymer dots includes the following steps:

[0079] Step 1: Dissolve different masses of ferric ions in deionized water to obtain ferric ion standard solutions of different concentrations (0~300μmol / L);

[0080] Step 2: By adding the above-mentioned ferric ion standard solution to ssHPA-CPDs aqueous solutions containing different amounts of flexible disulfide bonds, and incubating at 25℃ for 30 min, the fluorescence of a series of samples was detected using a fluorescence spectrophotometer. The linear relationship between the ferric ion concentration and the fluorescence value of ssHPA-CPDs was finally obtained, as shown below. Figure 4 As shown.

[0081] Figure 4 The horizontal axis represents the concentration of ferric ions, and the vertical axis represents the fluorescence quenching rate of ssHPA-CPDs. 0% ssHPA-CPD 25% ssHPA-CPD 50% ssHPA-CPD 75% ssHPA-CPD 100% This indicates that the number of flexible disulfide bonds in ssHPA-CPDs gradually increases, from Figure 4It can be seen that with the increase of ferric ion concentration, the fluorescence intensity of the solution is significantly quenched, and both show a good linear relationship. Furthermore, with the increase of disulfide bond content, the flexibility of the main chain is enhanced, and ssHPA-CPD with the highest disulfide bond content... 100% It exhibits optimal iron ion response and fluorescence changes.

[0082] Principle Analysis: On one hand, the abundant hydroxyl (-OH), carboxyl (-COOH), and amino (-NH2) groups, as well as other oxygen-containing functional groups, on the surface of ssHPA-CPDs readily coordinate with ferric ions. This results in a large number of electrons transferring from the excited state of ssHPA-CPDs to the half-filled 3d orbitals of ferric ions, leading to non-radiative electron-hole recombination and fluorescence quenching. Furthermore, the addition of ferric ions reduces the fluorescence lifetime of ssHPA-CPDs from 10.86 ns to 10.57 ns, accompanied by a significant change in the UV-Vis absorption spectrum, indicating that the quenching mechanism of ferric ions on ssHPA-CPDs is static quenching.

[0083] Experiment Example 4

[0084] The verification of the antibacterial effect of flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots includes the following steps:

[0085] Step 1: Weigh 12.5g of LB broth and dissolve it in an Erlenmeyer flask containing 50mL of deionized water. Sterilize the flask in an autoclave at 120℃ for 40min to obtain the liquid culture medium.

[0086] Step 2: Add 7.5g of agar to the liquid culture medium, sterilize, and you will get the solid culture medium.

[0087] Step 3: Add Escherichia coli and Staphylococcus aureus to liquid culture medium and incubate at 37°C for 24 hours. After centrifugation at 7000 rpm for 2 minutes, bacterial precipitate is obtained. Then, disperse the bacterial precipitate in PBS and adjust the absorbance OD600 to about 0.2 to obtain bacterial suspension.

[0088] Step 4: The concentrations of the ssHPA-CPDs prepared in this invention are serially diluted to 0.00625 mg / mL, 0.0125 mg / mL, 0.025 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL and 0.5 mg / mL, and cultured with Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli) for 24 h respectively.

[0089] Step 5: After incubation, dilute each group 10 times and add 100 μL to a solid culture medium plate. Spread the plate evenly using a spreader and incubate upside down in a 37°C incubator for 16 hours. Then, take photos to record the colony count and calculate the inhibition rate. The inhibition rate results are as follows: Figure 5 As shown.

[0090] The Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC 6538) used were commercially purchased standard strains.

[0091] Analysis of antibacterial mechanism: The numerous terminal amine groups of ssHPA-CPDs are positively charged under physiological conditions, which can bind to the negatively charged bacterial cell membrane, destroy the membrane structure, cause leakage of contents, and ultimately kill the bacteria.

[0092] The design concept of this invention for preparing flexible disulfide-modified hyperbranched polymer-based carbonized polymer dots via a hydrothermal solvent method is as follows: First, hyperbranched polyamide-amines (ssHPA) with varying disulfide bond content are prepared. Based on the fact that the bond length of the disulfide bond (S–S bond) is longer (~2.05 Å) than that of the C–C bond (~1.54 Å), and the bond energy (~268 kJ / mol) is lower than that of the C–C bond, and the bond angle is more flexible, resulting in improved molecular chain mobility and enhanced flexibility, a novel strategy is proposed to regulate the main chain flexibility of the hyperbranched polymer by changing the disulfide bond content. Using the flexible disulfide-modified hyperbranched polymer as the common source of nitrogen and sulfur dual heteroatoms, and citric acid as the carbon source, blue light-emitting nitrogen-sulfur dual heteroatom-doped carbonized polymer dots are prepared via a hydrothermal solvent method. The obtained nitrogen-sulfur dual heteroatom-doped carbonized polymer dots are then cooled, filtered, dialyzed, and freeze-dried to obtain nitrogen-sulfur dual heteroatom-doped carbonized polymer dopant powder. The powder was dissolved in pure water to obtain a nitrogen-sulfur dual-heteroatom-doped carbonized polymer dot solution. Then, the coordination interaction between ferric ions and the nitrogen-sulfur dual-heteroatom-doped carbonized polymer dots was utilized to achieve quantitative detection of ferric ions in food. Based on the fact that the numerous terminal amine groups of hyperbranched polyamide-amine carry a positive charge under physiological conditions, they can bind to the negatively charged bacterial cell membrane, disrupting the membrane structure, causing leakage of contents, and ultimately killing the bacteria. This invention utilizes a simple and rapid fluorescence response to achieve quantitative detection of ferric ions, thus avoiding complex and cumbersome operating procedures, long detection times, and the consumption of expensive equipment and experimental consumables.

[0093] Comparative Example 1

[0094] Same as Example 2, except that N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was not added in step three.

[0095] Comparative Example 2

[0096] Same as Example 2, except that in step four, the nanofiber membrane with a molecular weight cutoff of 1 kDa was not used for pre-filtration.

[0097] Comparative Example 3

[0098] Same as Example 2, except that: dialysis is performed in pure water using a dialysis bag with a molecular weight cutoff of 1000 Da, i.e., without strong acid cation exchange resin.

[0099] Comparative Example 4

[0100] A certain existing technology: carbonized polymer dots are prepared by hydrothermal reaction at 180°C for 8 hours using citric acid and hyperbranched polyimide as precursors; dialysis purification (molecular weight cutoff of 1000 Da) is performed without the use of ion exchange resin; no surface modification or disulfide bond modification is performed.

[0101] Example 4

[0102] Similar to Example 2, except that in step three, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane needs to be pre-hydrolyzed before addition: N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and anhydrous ethanol are mixed at a volume ratio of 1:5, and L-cysteine ​​hydrochloride-sodium citrate buffer solution with pH=2.0 is added until the final concentration of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 0.1 mol / L. The mixture is then magnetically stirred in an ice-water bath at 0~5℃ for 5~10 minutes to obtain the pre-hydrolyzed solution.

[0103] Slowly heat the pre-hydrolyzed solution to 50°C and add it dropwise to the hydrothermal reaction system in step three within 30 minutes, with the drop rate controlled at 0.5 mL / min to 2 mL / min. After the drop is completed, heat the reaction system to 80 to 150°C and continue the reaction for 1 to 8 hours to complete the surface-oriented modification.

[0104] Example 5

[0105] Similar to Example 4, except that the pre-hydrolyzed solution needs to undergo the following treatment before being added to the reaction system in step three:

[0106] The pre-hydrolyzed solution was placed in a rotary evaporator at 30-35℃ with a vacuum of -0.09-0.1 MPa. Ethanol was removed by distillation until the volume of the distillate reached 45%-50% of the initial volume of the pre-hydrolyzed solution. HMDS and 0.1 wt% PEG-2000 were added to the concentrate, with the amount of HMDS added being 0.1-0.3 times the volume of the concentrate. The mixture was stirred at 0-5℃ for 20-30 minutes. The treated pre-hydrolyzed solution was then added dropwise to the reaction system under nitrogen protection within 30 minutes.

[0107] Example 6

[0108] Similar to Example 5, except that in the rotary evaporation process for removing ethanol, the vacuum degree is controlled at -0.095±0.002 MPa; the distillation endpoint is determined by the viscosity of the concentrate reaching 50±2 cP, and the viscosity is measured at 25°C using a Brookfield viscometer (rotor LV3, rotation speed 60 rpm).

[0109] Example 7

[0110] Same as Example 6, except that the mass ratio of HMDS to PEG-2000 is 1:0.8 to 1:1; the endpoint of the stirring reaction is determined by the pH value of the reaction solution rising to 6.5±0.2, and a covalently cross-linked network coating structure of siloxane and polyethylene glycol is generated.

[0111] The properties of the flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots prepared in the above embodiments and comparative examples were tested. The specific test methods included:

[0112] 1. Fluorescence performance test

[0113] Quantum yield (QY) was determined using quinine sulfate as a standard reference at an excitation wavelength of 350 nm; fluorescence stability was assessed by recording the intensity retention rate of a 1 mg / mL aqueous solution after continuous irradiation with a 365 nm UV lamp for 24 hours.

[0114] 2.Fe 3+ Detection performance test

[0115] The limit of detection (LOD) is based on the fluorescence change rate (ΔF / F0) and Fe. 3+ The linear relationship of concentration was calculated based on 3 times the standard deviation of the blank signal; anti-interference performance was tested with 10 times the concentration of Na. + K + Ca 2+ Mg 2+ Fe 2+ The determination is made based on whether the fluorescence change rate under plasma exceeds 5%.

[0116] 3. Antibacterial performance test

[0117] Minimum inhibitory concentration (MIC) 90 The lowest concentration that inhibited the growth of 90% of Escherichia coli was determined by plate counting method; the inhibition rate was the percentage reduction of colonies after 24 hours of treatment with a sample of 0.1 mg / mL.

[0118] 4. Stability and reproducibility testing

[0119] Water dispersion stability was characterized by the sedimentation rate and dynamic light scattering (DLS) particle size increase after standing for 30 days in a 1 mg / mL aqueous solution; batch reproducibility was determined by testing 100 μM Fe in three independently prepared batches of samples. 3+The relative standard deviation (RSD) of fluorescence intensity is used to measure it.

[0120] Performance test results comparison and analysis:

[0121] Example 2 (optimal disulfide bond density) exhibited the highest fluorescence quantum yield (29.08%), the lowest Fe³⁺ detection limit (0.07 μM), and the strongest antibacterial activity (MIC). 90 =0.05 mg / mL), thanks to its high-density disulfide bond structure resulting from its pure bisacryloylcysteine ​​formulation (HMBA:CBA=0.1:4). The disulfide bond length (2.05 Å) is significantly longer than that of the C-C bond (1.54 Å), with a lower bond energy (268 kJ / mol) and more flexible bond angles, giving the molecular chain stronger mobility, thereby improving radiative transition efficiency (high QY) and coordination site accessibility (low LOD). At the same time, the reactive oxygen species (ROS) generated by the reduction of disulfide bonds by glutathione in bacteria synergistically enhance the antibacterial effect with the positive charge of the amino groups.

[0122] In Example 1 (without disulfide bonds), the rigid main chain restricts electron movement, resulting in a decrease in QY to 25%, and the lack of sulfur coordination sites leads to an increase in LOD to 1.2 μM.

[0123] Example 3 (mixing ratio 1:1) has insufficient disulfide bond density and its performance is between the two (QY 27%, LOD 0.5μM).

[0124] Example 4, based on Example 2, adds a "silane pre-hydrolysis treatment" (pH=2.0 buffer solution, stirring at 0-5℃) to convert silane into active silanol (Si-OH), achieving directional bonding rather than physical adsorption. Performance improvements: precipitation rate decreased from 15% to 8%, uniform coating reduced surface energy differences, and inhibited aggregation; fluorescence stability increased from 92% to 95%, reducing non-radiative quenching caused by surface defects; batch RSD decreased from 4.2% to 3.5%, improving coating consistency. The pre-hydrolysis treatment in Example 4 solves the "random adsorption of silane" problem of Example 2 and optimizes stability.

[0125] Example 5, based on Example 4, adds "crosslinking of HMDS and PEG-2000" (mass ratio 1:0.5~1:1, reaction at 0-5℃) to form a covalent three-dimensional network of siloxane and polyethylene glycol. Performance improvements: particle size increase decreased from +12nm to +10nm, the crosslinked network enhances steric hindrance; precipitation rate decreased from 8% to 7%, the network structure improves colloidal stability; fluorescence stability increased from 95% to 96%. The crosslinked network in Example 5 compensates for the "insufficient mechanical strength of the coating layer" in Example 4, further inhibiting aggregation.

[0126] Direct addition of silane coupling agents to hydrothermal systems can easily lead to self-agglomeration, resulting in uneven surface modification. By pre-hydrolyzing to generate active silanol (Si-OH), followed by rotary evaporation to remove ethanol (to avoid bubble defects), and then constructing a three-dimensional network through HMDS / PEG crosslinking, a dense coating layer can be formed (XPS confirmed a coating rate of ≥5%), reducing fluorescence quenching and increasing the exposure rate of antibacterial groups (Experimental Example 4).

[0127] Example 6, based on Example 5, changed the distillation endpoint from volume ratio to viscosity control (50±2 cP, measured with a Brookfield viscometer) to precisely regulate the degree of silane polymerization. Performance improvements include: a reduction in precipitation rate from 7% to 5%, and a viscosity threshold that prevents uneven addition due to an overly thick pre-hydrolyzed solution; a reduction in particle size increase from +10 nm to +8 nm, allowing for controllable polymerization rate and preventing excessive local crosslinking; and a reduction in batch RSD from 3.0% to 2.5%, improving reaction uniformity. The viscosity control in Example 6 addresses the "unquantifiable degree of polymerization" defect of Example 5, improving process reproducibility.

[0128] Example 7 adds a "reaction endpoint pH determination" (pH=6.5±0.2) to Example 6, marking complete hydrolysis and cross-linking of HMDS. Performance improvements: Particle size increase decreased from +8nm to +6nm, side reactions decreased, and coating integrity improved; fluorescence stability increased from 97% to 98%, residual unreacted silane was eliminated, and quenching sites were reduced; batch RSD decreased from 2.5% to 2.2%, the reaction endpoint was clearly defined, and batch fluctuations were reduced. The pH determination in Example 7 addresses the "ambiguity of reaction degree" problem in Example 6.

[0129] Comparative Example 1 (without silane modification) showed a decrease in QY to 18% due to increased surface defects. The oxidation of uncoated amine groups caused Fe... 3+ The decreased coordination ability and severe aggregation leading to a precipitation rate of 45% demonstrate the necessity of silane modification for functionality and stability.

[0130] Comparative Example 2 (without pre-filtration) experienced secondary aggregation due to residual macromolecular impurities, resulting in a batch RSD of 9.7%. Furthermore, the impurities covered the active amine groups, reducing the antibacterial rate to 82%, highlighting the crucial role of pre-filtration in purity and reproducibility.

[0131] Comparative Example 3 (without ion exchange resin) residual Ca after dialysis 2+ Mg 2+ Competition Fe 3+ The binding site caused the LOD to degrade to 4.2 μM, and the anti-interference failed.

[0132] The drawbacks of Comparative Example 4 (existing technology: rigid carbon chain without disulfide bond modification) are more representative: the rigid backbone restricts molecular motion, with a QY of only 8% (far lower than the 29.08% of Example 2); the lack of disulfide bonds and amino groups results in low antibacterial activity (MIC).90 =0.50mg / mL); the aggregation problem remains unresolved, with a precipitation rate as high as 50% after 30 days and a batch RSD of 18.0%, which cannot meet the needs of practical applications.

[0133] This invention overcomes the inherent defects of traditional carbonized polymer dots through molecular structure design and process innovation:

[0134] 1. Disulfide bond flexible backbone (core of Example 2): By maximizing the disulfide bond density (HMBA:CBA=0.1:4), electronic transition paths and coordination space are controlled at the atomic level to achieve QY 29.08%, LOD 0.07 μM, and MIC 90 Synergistic enhancement at 0.05 mg / mL;

[0135] 2. Surface orientation modification process (paths of Examples 4-7):

[0136] Pre-hydrolysis treatment ensures uniform silane coating (precipitation rate reduced by 46.7%).

[0137] HMDS / PEG crosslinking enhances steric hindrance (reducing particle size increase by 64%).

[0138] The pre-hydrolysate validation step (coverage rate ≥ 5.0%) overcomes the reproducibility challenge (RSD reduced by 57%).

[0139] 3. Performance advantages over existing technologies: All key performance indicators (QY, LOD, antibacterial activity, stability) surpass those of comparative example 4.

[0140] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.

Claims

1. A method for preparing flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots, characterized in that, Includes the following steps: Step 1: Dissolve a mixture of 1,6-hexanediamine and bisacryloylcysteine ​​in methanol and mix thoroughly. Then carry out a nitrogen-Michael addition reaction at 25°C to 35°C for 48 to 96 hours under nitrogen atmosphere to prepare hyperbranched polyamide-amine with disulfide bonds. The molar ratio of the mixture of 1,6-hexanediamine and bisacryloylcysteine ​​to tris(2-aminoethyl)amine is 1:1.1 to 1:1.2; the molar ratio of 1,6-hexanediamine to bisacryloylcysteine ​​in the mixture is 0.1:4 to 4:0.

1. Step 2: Add 0.05-0.2 mol / L L-cysteine ​​hydrochloride-sodium citrate buffer dropwise to the product obtained in Step 1 until pH=2. After vacuum filtration, dry the product under vacuum at 40°C for 24 to 48 hours to obtain white or light yellow hyperbranched polyamide-amine hydrochloride powder. Step 3: Mix citric acid with the hyperbranched polyamide-amine hydrochloride powder at a mass ratio of 2:5 to 10:3, using pure water as a solvent, and carry out a hydrothermal reaction at 80°C to 150°C for 1 to 8 hours; simultaneously add N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, wherein the mass of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 5% to 15% of the citric acid. Step 4: After cooling the reaction product to room temperature, filter it. First, pre-filter it through a cellulose ester membrane with a molecular weight cutoff of 1 kDa, and then dialyze it for 24 to 48 hours in a circulating pure water system containing a strong acid cation exchange resin using a dialysis bag with a molecular weight cutoff of 800 to 1000 Da. After freeze-drying the dialysate, flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots are obtained. The number of disulfide bonds in the carbonized polymer sites of the flexible disulfide bond-modified hyperbranched polymer was controlled by adjusting the molar ratio of 1,6-hexanediamine to bisacryloylcysteine.

2. The method for preparing flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots as described in claim 1, characterized in that, In step one, the molar ratio of the mixture of 1,6-hexanediamine and bisacryloylcysteine ​​to tris(2-aminoethyl)amine was 1:1.1, and the reaction conditions were 25°C and 50 h under nitrogen protection.

3. The method for preparing flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots as described in claim 1, characterized in that, In step three, the mass ratio of citric acid to hydrochloride powder is 2:1, the reaction temperature is 130℃, and the reaction time is 6 hours.

4. The method for preparing flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots as described in claim 1, characterized in that, Before adding N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, it needs to be pre-hydrolyzed: N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and anhydrous ethanol are mixed at a volume ratio of 1:5, and L-cysteine ​​hydrochloride-sodium citrate buffer solution with pH=2.0 is added until the final concentration of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is 0.1 mol / L. The mixture is then magnetically stirred in an ice-water bath at 0~5℃ for 5~10 minutes to obtain the pre-hydrolyzed solution. Slowly heat the pre-hydrolyzed solution to 50°C and add it dropwise to the hydrothermal reaction system in step three within 30 minutes, with the drop rate controlled at 0.5 mL / min to 2 mL / min. After the drop is completed, heat the reaction system to 80 to 150°C and continue the reaction for 1 to 8 hours to complete the surface-oriented modification.

5. The method for preparing flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots as described in claim 4, characterized in that, The pre-hydrolyzed solution needs to be treated as follows before being added dropwise to the reaction system in step three: The pre-hydrolyzed solution was placed in a rotary evaporator at 30-35℃ with a vacuum of -0.09-0.1 MPa. Ethanol was removed by distillation until the volume of the distillate reached 45%-50% of the initial volume of the pre-hydrolyzed solution. Hexamethyldisilazane and 0.1 wt% polyethylene glycol-2000 were added to the concentrate. The amount of hexamethyldisilazane added was 0.1-0.3 times the volume of the concentrate. The mixture was stirred at 0-5℃ for 20-30 minutes. The pre-hydrolyzed solution was then added dropwise to the reaction system under nitrogen protection within 30 minutes.

6. The method for preparing flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots as described in claim 5, characterized in that, In the rotary evaporation process for removing ethanol, the distillation endpoint is determined by the concentration of the concentrate reaching 50 ± 2 cP, which is measured using a Brookfield viscometer at 25°C.

7. The method for preparing flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots as described in claim 5, characterized in that, The mass ratio of hexamethyldisilazane to polyethylene glycol-2000 is 1:0.8 to 1:1; the stirring reaction is carried out at 0-5°C, and the reaction endpoint is determined by the pH value of the reaction solution rising to 6.5±0.2, and a covalently cross-linked network coating structure of siloxane and polyethylene glycol is generated.

8. The application of flexible disulfide bond-modified hyperbranched polymer-based carbonized polymer dots prepared by the preparation method according to any one of claims 1 to 7 in the quantitative detection of trivalent iron ions in meat by-products, characterized in that, The method includes the following steps: adding a 0-300 μmol / L standard solution of ferric ions to an aqueous solution of flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots, mixing, incubating at 25°C for 30 min, and then detecting the change in fluorescence intensity using a fluorescence spectrophotometer to establish a linear relationship model between ferric ion concentration and fluorescence intensity; the disulfide bond content in the flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots is positively correlated with the detection sensitivity of ferric ions.

9. The application of flexible disulfide bond-modified hyperbranched polymer-based carbonized polymer dots prepared by the preparation method according to any one of claims 1 to 7 in antibacterial activity, characterized in that, The concentration of flexible disulfide bond modified hyperbranched polymer-based carbonized polymer dots is ≥0.05 mg / mL.

Citation Information

Patent Citations

  • Preparation method and application of AIE type hyperbranched polymer gold cluster material

    CN113030043A

  • Thiol flavor response type hyperbranched polymer copper cluster as well as preparation method and application thereof

    CN118562125A